An Enhanced Video Assisted Health Education System - et. al., Djumanova Aijan Baxtiyarovna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article deals with the problem of implementing management accounting in the domestic practice of logistics systems. Which is of paramount importance due to the need for in-depth research of the economic nature, essence and content of management accounting, its fundamental theoretical foundations, for making informed management decisions.